Relationship Between HIV/AIDS Information Sources and Premature Sexual Knowledge in Adolescents - Angela Librianty Thome (Indonesian Journal of Global Health Research, 2025)
The issue of HIV/AIDS among adolescents is still relatively high and has quite an impact on the reproductive health of adolescents themselves. Adolescents are at risk of having premarital sex so that HIV/AIDS transmission can occur. Adolescents are also an age group that uses a lot of social media to access all kinds of information, one of which is HIV/AIDS. So with this information, adolescents increasingly understand the importance of avoiding premarital sexual incidents. This study aims to explain whether or not there is a relationship between sources of HIV/AIDS information obtained by adolescents and premarital sexual knowledge. This study uses a cross-sectional design with the Proportionate Stratified Random Sampling technique to 136 respondents (adolescents). Data collection uses instruments that have been tested valid and reliable through Spearman’s Rho Correlation. There is a relationship between sources of HIV/AIDS information and premarital sexual knowledge in adolescents with a p-value < alpha. It turns out that sources of HIV/AIDS information are related to premarital sexual knowledge because adolescents can avoid premarital sexual incidents to avoid contracting HIV/AIDS.